2018
DOI: 10.1016/j.cmi.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium innocuum is a vancomycin-resistant pathogen that may cause antibiotic-associated diarrhoea

Abstract: Vancomycin-resistant C. innocuum may play a potential role as a causative agent of AAD. The clinical manifestations of AAD caused by C. innocuum were diarrhoea or severe colitis, including pseudomembranous colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 25 publications
0
40
0
2
Order By: Relevance
“…The increased abundance of Clostridium innocuum after antibiotic treatment in all diet groups can be attributed to its ability to produce peptidoglycan precursors with a C-terminal serine, which have a low affinity for vancomycin (57). This organism's resistance to vancomycin is a potential cause of antibiotic-associated diarrhea in humans, with effects similar to those seen with CDI (58).…”
Section: Effect Of a High-fat/low-protein Keto-like Diet On Antibiotimentioning
confidence: 99%
“…The increased abundance of Clostridium innocuum after antibiotic treatment in all diet groups can be attributed to its ability to produce peptidoglycan precursors with a C-terminal serine, which have a low affinity for vancomycin (57). This organism's resistance to vancomycin is a potential cause of antibiotic-associated diarrhea in humans, with effects similar to those seen with CDI (58).…”
Section: Effect Of a High-fat/low-protein Keto-like Diet On Antibiotimentioning
confidence: 99%
“…There were several important differences in the canine training and the evaluation methods that may account for the observed difference in results [3] . In this study, canister work (the scent carousel) was used exclusively for the inter-rater reliability assessment in order to evaluate only odour recognition and not search capability [5] , [8] , [9] . In addition, the Vancouver Coastal Health canine teams used scent pads that contained only the odour of the CD-positive faecal specimens or the distractor (CD-negative specimens) rather than the actual faeces.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chia and colleagues reported that C. innocuum is the second most common clostridial species causing extraintestinal infection ( 2 ) and is a cause of a Clostridioides difficile -like intestinal infection ( 3 ). These isolates were vancomycin resistant, cytotoxic to Vero and HT-29 cells, and enteropathogenic in mice ( 3 ). With this reconsideration of C. innocuum pathogenicity, the complete genome sequence of strain ATCC 14501 is needed.…”
Section: Announcementmentioning
confidence: 99%